2021
DOI: 10.1038/s41598-020-80434-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological performance and oviposition preference of tomato pinworm Tuta absoluta when offered a range of Solanaceous host plants

Abstract: The tomato pinworm Tuta absoluta (Lepidoptera: Gelechuidae) is native to South America and has now become the main tomato pest in Europe, Africa and Asia. The wide range of host plants attacked by this pest has been reported as one of the main reasons for the success of this important insect species. However, the information currently available on the biological performance of T. absoluta on Solanaceae has been obtained from a limited number of host species. The Solanaceae family is composed of thousands of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Tomato cultivars influence the oviposition preference by T. absoluta females and the biological performance of the insect 24 , 25 , as well as its population density and distribution pattern in the field 26 . Proffit et al 27 reported that a wild tomato cultivar, Solanum habrochaites , was avoided by ovipositing T. absoluta , whereas the cultivated tomato cultivar, Solanum lycopersicum , like cv.…”
Section: Introductionmentioning
confidence: 99%
“…Tomato cultivars influence the oviposition preference by T. absoluta females and the biological performance of the insect 24 , 25 , as well as its population density and distribution pattern in the field 26 . Proffit et al 27 reported that a wild tomato cultivar, Solanum habrochaites , was avoided by ovipositing T. absoluta , whereas the cultivated tomato cultivar, Solanum lycopersicum , like cv.…”
Section: Introductionmentioning
confidence: 99%
“…The pest has since spread widely to ~110 countries in Africa, America, Asia, Europe, and the Middle East through the large-scale importation of tomatoes in those countries (Desneux et al, 2010 ; Biondi et al, 2018 ; Mansour et al, 2018 ; Guimapi et al, 2020 ). Tuta absoluta feeds, overwinters, and breeds on a broad range of hosts such as eggplant, potato, nightshade, tomato, and tobacco (Silva et al, 2021 ). Tomato is reported to be the most preferred host (Shah et al, 2015 ; Negi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been investigating the various mechanisms of T. absoluta infestations in tomatoes and other species (Desneux et al, 2010 ; Cherif and Verheggen, 2019 ; Silva et al, 2021 ). In our earlier studies, the T. absoluta growth and survival rate in tomatoes was found to be substantially higher than in eggplants (Li Xiaowei, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, there are some nightshades species resistant to tomato leafminer attack, as Capsicum annuum L., and Capsicum chinense Jacquin var. Cumari do Pará (Silva et al, 2021), and some species inside the Solanum genus, as different species of wild tomatoes: S. habrochaites S. Knapp & D.M. Spooner (de Oliveira et al, 2020;Silva et al, 2021), S. cheesmaniae (Riley) Fosburg (Rakha et al, 2017;Han et al, 2018c).…”
Section: Solanaceous Resistance Against Tuta Absolutamentioning
confidence: 99%
“…Cumari do Pará (Silva et al, 2021), and some species inside the Solanum genus, as different species of wild tomatoes: S. habrochaites S. Knapp & D.M. Spooner (de Oliveira et al, 2020;Silva et al, 2021), S. cheesmaniae (Riley) Fosburg (Rakha et al, 2017;Han et al, 2018c). Wild relatives of 4 tomatoes are today the main source of the identified resistance traits for tomato breeders.…”
Section: Solanaceous Resistance Against Tuta Absolutamentioning
confidence: 99%